Pengaruh Ukuran Perusahaan, Profitabilitas, Laba / Rugi Operasi, Opini Auditor, dan Reputasi Kap Terhadap Audit Delay - Nurmalita, Fika; , Drs.Atwal Arifin, Akt.,M.Si (2016)
This study aims to provide empirical evidence of influence: Company Size, Profitability, Profit / Loss Operations, Audit Opinion and Reputation Audit Firm to Delay in Manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2011-2014. This research was conducted using secondary data. The population in this study were 105 companies listed on the Indonesian Stock Exchange (BEI) during the period 2011-2012. The analytical method used is logistic regression analysis. The results of this study prove that the variables company size, profitability, Auditor Opinion and Reputation KAP effect on Audit Delay, while the variable profit / loss does not affect the operation of the Audit Delay in manufacturing companies in the Indonesia Stock Exchange (BEI).